2021
DOI: 10.1071/pc21058
|View full text |Cite
|
Sign up to set email alerts
|

Introduced red foxes (

Abstract: It has been asserted that introduced red foxes (Vulpes vulpes) destroy ~95% of nests of freshwater turtles in south-eastern Australia, are more efficient predators of freshwater turtle nests than Australian native predators, and are driving Australian freshwater turtle species to extinction. Available information was reviewed and analysed to test these assertions. Nest predation rates for all predators including foxes averaged 70% across Australia and 76% for south-eastern Australia compared to 72% for North A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…Studies of turtle nest predation may be biased by differing detectability of intact and raided nests by human observers (Chessman, 2022). Raided nests are more visible and evident for a longer period than intact nests or exit holes, and exit holes are more visible and evident for longer than intact nests.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of turtle nest predation may be biased by differing detectability of intact and raided nests by human observers (Chessman, 2022). Raided nests are more visible and evident for a longer period than intact nests or exit holes, and exit holes are more visible and evident for longer than intact nests.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying predators is also important because there may be rare predatory species among them, such as, e.g., Eurasian otter or European wildcat ( Felis silvestris Schreber, 1775). It is only based on knowledge of egg predators that appropriate loss-reducing measures can be taken for conservation management [ 49 , 71 , 72 , 73 ]. European pond turtles are characterized by habitat fidelity and longevity [ 74 , 75 , 76 ], which is why females try to lay eggs in the same place for several years, despite high predation pressure [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thompson (1983) also noted that Cooper Creek had a high number of juveniles compared to E. m. macquarii populations in the Murray River and suggested that this was a result of differences in nest predation rates by invasive foxes ( Vulpes vulpes ), which are common and abundant around the Murray River, but rare or absent around Cooper Creek. Subsequent research also found low proportions of juveniles in the Murray River (Chessman, 2011; Van Dyke et al, 2019); however, the role of foxes in that trend is not universally accepted (Chessman, 2021). It would be useful to systematically examine nest predation rates by natural nest predators at Cooper Creek.…”
Section: Discussionmentioning
confidence: 99%